Genetic characteristics of a wheat founder parent and a widely planted cultivar derived from the same cross - Li-fang CHANG; Hui-hui LI; Xiao-yang WU; Yu-qing LU; Jin-peng ZHANG; Xin-ming YANG; Xiu-quan LI; Wei-hua LIU; Li-hui LI (Journal of Integrative Agriculture, 2018)
Founder parents have contributed significantly to the improvement of wheat breeding and production. In order to investigate the genetic characteristics of founder parents and widely planted cultivars, Mazhamai (M), Biyumai (B) and six sibling lines (BM1–6) derived from the cross M×B were phenotyped for eight yield-related traits over multiple years and locations and genotyped using the the wheat 90K single nucleotide polymorphism (SNP) assay. BM4 has been used as a founder parent, and BM1 has been widely planted, whereas BM2, 3, 5, and 6 have not been used extensively for breeding or planting in China. Phenotypic comparisons revealed that BM4 and BM1 displayed a better overall performance than the other sibling lines. BM1 showed higher thousand-grain weight than BM4, whereas BM4 exhibited lower coefficient of variation for most of the yield-related traits across different years and locations, indicating that BM4 was widely adaptable and more stable in different environments. SNP analysis revealed that BM4 and BM1 inherited similar proportions of the M genome but are dissimilar to BM2, 3, 5, and 6. Both BM1 and BM4 have specific alleles that differ from the other BM lines, and most of these alleles are concentrated in specific chromosomal regions that are found to associate with favorable QTLs, these SNPs and their surrounding regions may carry the genetic determinants important for the superior performance of the two lines. But BM4 has more genetic diversity than BM1 with more specific alleles and pleiotropic regions, indicating that the genome of BM4 may be more complex than the other sibling lines and has more favorable gene resources. Our results provide valuable information that can be used to select elite parents for wheat and self-pollinating crop breeding.